Depressive symptoms mediate the relationship between cognitive reserve and cognitive performance in middle-aged and older Chinese adults: evidence from population-based and clinical PET cohorts including cognitively normal and cognitively impaired participants - Gu, Yucheng; Li, Xiaoyuan; Chen, Nihong; Wang, Feng (Frontiers in Aging Neuroscience, 2026)
BackgroundCognitive reserve (CR) may protect cognitive performance under pathology. Depressive symptoms are common in mid and late life and are linked to poorer cognition. This study investigated whether depressive symptoms mediate the association between CR and both global and domain-specific cognitive performance in middle-aged and older Chinese adults.MethodsData from 1,636 participants in the 2018 wave of the China Health and Retirement Longitudinal Study (the CHARLS 2018 cohort) were analyzed. Information from an independent retrospective cohort that underwent amyloid and tau positron emission tomography (PET) at Nanjing First Hospital (the PET cohort; n = 100) was collected to validate the results from CHARLS. Associations between CR and cognitive performance in memory, executive function, language were examined, and mediation analysis was performed to assess the role of depressive symptoms. Subgroup analyses were also conducted. In the CHARLS 2018 cohort, participants were stratified as cognitively normal or cognitively impaired. In the PET cohort, participants were stratified into amyloid-negative cognitively normal and amyloid-positive mild cognitive impairment (MCI).ResultsAcross both cohorts, higher CR was associated with a lower risk of cognitive impairment and better domain-specific performance. Depressive symptoms partially mediated the association between CR and several domains of cognition in the analyses of the overall cohorts. In both the CHARLS 2018 subgroups, no mediation was detected. In the PET cohort, depressive symptoms fully mediated the effects of CR on executive function and attention in the MCI group, in which most participants showed tau deposition on PET, whereas no mediation was observed in the cognitively normal subgroup.ConclusionCR is a protective factor for cognition, and depressive symptoms act as a modifiable mediator. In AD patients with confirmed tau pathology, timely detection and management of depressive symptoms may help preserve cognition and enhance the benefits of CR.